2010
DOI: 10.1111/j.1365-2621.2010.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plant oils for suppression of crown rot disease and improvement of shelf life of banana (Musa spp. AAA subgroup, cv. Robusta)

Abstract: Fourteen plant oils were evaluated to control the crown rot disease caused by Lasiodiplodia theobromae and Colletotrichum musae. Five of these, viz. Ocimum sanctum, Cymbopogan citratus, C. martinii, C. nardus and Pelargonium graveolens oils completely arrested the mycelial growth of both test pathogens at their lowest concentration compared to other oils. Besides, these plant oils have also inhibited the activity of cellulolytic and pectinolytic enzymes produced by these pathogens effectively under in vitro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Results obtained in present study are in conformity with findings of Ranasinghe et al, (2002) who suggested clove and cinnamon essential oils as alternative postharvest treatments for banana anthracnose. Meanwhile in another study by Sangeetha et al, (2010), treatment of banana fruit variety Robusta (Cavendish) with oils of lemongrass and tulasi had not only reduced the crown rot severity significantly, but also increased the shelf life of banana fruits. The potential of using essential oils by spraying or dipping to control postharvest decay has been examined in fruit and vegetables (Dixit et al, 1995).…”
Section: In Vivo Evaluation Of Oilsmentioning
confidence: 95%
“…Results obtained in present study are in conformity with findings of Ranasinghe et al, (2002) who suggested clove and cinnamon essential oils as alternative postharvest treatments for banana anthracnose. Meanwhile in another study by Sangeetha et al, (2010), treatment of banana fruit variety Robusta (Cavendish) with oils of lemongrass and tulasi had not only reduced the crown rot severity significantly, but also increased the shelf life of banana fruits. The potential of using essential oils by spraying or dipping to control postharvest decay has been examined in fruit and vegetables (Dixit et al, 1995).…”
Section: In Vivo Evaluation Of Oilsmentioning
confidence: 95%
“…Citronella oil emulsified coating might have reduced the surface moisture loss and maintained the fruit firmness. High firmness of Robusta banana was found to get maintained with post harvest application of Citronella oil at ambient storage (Sangeetha et al 2010). Skin colour of mango cv.…”
Section: Resultsmentioning
confidence: 91%